CD38 prognostic role in chronic lymphocytic leukemia patients treated with standard chemotherapy or targeted agents: a monocentric real-life experience - Mettivier, Laura; De Novellis, Danilo; Della Corte, Anna Maria; Serio, Bianca; Pezzullo, Luca; Guariglia, Roberto; Ferrara, Idalucia; Fontana, Raffaele; Martorelli, Maria Carmen; Luponio, Serena; Buonanno, Maria Teresa; Marcucci, Rossella; et al. (Frontiers in Oncology, 2025)
IntroductionTherapeutic strategies for patients affected by Chronic Lymphocytic Leukemia (CLL) have undergone significant changes over the last decade, shifting from chemoimmunotherapy to targeted therapy.MethodsThis retrospective, single-center, real-word study aims to identify candidate prognostic markers in 230 consecutive CLL patients treated with standard chemoimmunotherapies or targeted agents from July 2011 to June 2023.ResultsPatients receiving targeted therapy were more likely to have mutated IGHV, while those with a CD38+CD49d+ CLL immunophenotype showed an increased risk of refractoriness and disease recurrence, as demonstrated by multivariate analysis. Conversely, CLL patients with a CD38-CD49d- phenotype received great benefits when treated with targeted agents, whereas advanced age was a negative risk factor for patients treated with standard chemotherapy.ConclusionsIn conclusion, CD38 expression emerges as a key prognostic marker in CLL, reinforcing the need to integrate clinical, biological, phenotypic, and molecular factors into treatment decision-making and both standard chemotherapy and targeted regimens remain effective in real-life settings.